A Randomised, Cross-Over, Placebo-Controlled Study of Aloe vera in Patients with Irritable Bowel Syndrome: Effects on Patient Quality of Life. (5th October 2010) - Hutchings, H. A.; Wareham, K.; Baxter, J. N.; Atherton, P.; Kingham, J. G. C.; Duane, P.; Thomas, L.; Thomas, M.; Ch'ng, C. L.; Williams, J. G.
Abstract : Background . Irritable bowel syndrome (IBS) is a chronic, difficult to treat condition. The efficacy of Aloe vera in treating IBS symptoms is not yet proven. The purpose of this study was to determine if Aloe vera is effective in improving quality of life. Methods . A multicentre, randomised, double-blind, cross-over placebo controlled study design. Patients were randomised to Aloe vera, wash-out, placebo or placebo, washout, Aloe vera . Each preparation (60 mL) was taken orally twice a day. Patient quality of life was measured using the Gastrointestinal Symptoms Rating Score, Irritable Bowel Syndrome Quality of Life, EuroQol and the Short-Form-12 at baseline and treatment periods 1 and 2. Results . A total of 110 patients were randomised, but only 47 completed all questionnaires and both study arms. Statistical analysis showed no difference between the placebo and Aloe vera treatment in quality of life. Discussion. This study was unable to show that Aloe vera was superior to placebo in improving quality of life. Drop outs and other confounding factors may have impacted on the power of the study to detect a clinically important difference. Conclusion . This study failed to find Aloe vera superior to placebo in improving quality of life proven Irritable Bowel Syndrome patients.